2007
DOI: 10.1093/toxsci/kfm124
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Key Genes Regulating Gonadal Steroidogenesis in Control and Ketoconazole- or Vinclozolin-Exposed Fathead Minnows

Abstract: This study evaluated changes in the expression of steroidogenesis-related genes in male fathead minnows exposed to ketoconazole (KTC) or vinclozolin (VZ) for 21 days. The aim was to evaluate links between molecular changes and higher level outcomes after exposure to endocrine-active chemicals (EACs) with different modes of action. To aid our analysis and interpretation of EAC-related effects, we first examined variation in the relative abundance of steroidogenesis-related gene transcripts in the gonads of male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Previous studies with fathead minnows (Pimephales promelas) found that the expression of both StAR and 3β-HSD were significantly altered by both age and GSI [34]. Even when these factors were taken into account, the exposure of fathead minnows to the antiandrogen ketoconazole (4, 25, 100, and 400 µg/L) resulted in significantly increased expression of StAR in the testes of male fathead minnows exposed to concentrations of 6 and 400 µg/L.…”
Section: Plasma Hormone Concentrations Spiggin Concentrations and Rmentioning
confidence: 93%
“…Previous studies with fathead minnows (Pimephales promelas) found that the expression of both StAR and 3β-HSD were significantly altered by both age and GSI [34]. Even when these factors were taken into account, the exposure of fathead minnows to the antiandrogen ketoconazole (4, 25, 100, and 400 µg/L) resulted in significantly increased expression of StAR in the testes of male fathead minnows exposed to concentrations of 6 and 400 µg/L.…”
Section: Plasma Hormone Concentrations Spiggin Concentrations and Rmentioning
confidence: 93%
“…Assays for most of the genes noted above have been described elsewhere (Villeneuve et al, 2006(Villeneuve et al, , 2007aMartinovic et al, 2008). However, QPCR assays for fathead minnow gnrhr1, gnrhr3, and cyp51 are reported here for the first time.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were amplified over 40 cycles (melt 94°C for 20 s, anneal and extend, 58°C for 60 s) using a 7500 RT-PCR System. As above, relative transcript abundance was estimated based on a standard curve generated by analyzing multiple dilutions of a gene-specific amplicon, without correction for amplification efficiency (for details on preparation of gene-specific standards for Taqman assays, see Villeneuve et al, 2007a).…”
Section: Methodsmentioning
confidence: 99%
“…A standard curve of known quantities of a gene-specific mRNA standard (10-fold dilution series; generally 20-2 × 10 7 copies) was used to calibrate the QPCR data and estimate the number of gene-specific transcripts per ng total RNA. Details regarding the specific primer and probe sequences used and the methods for preparing gene-specific mRNA standards have been reported previously (Villeneuve et al, 2006(Villeneuve et al, , 2007(Villeneuve et al, , 2009aMartinovic et al, 2008). Due to potential differences in amplification and probe binding efficiencies between total RNA samples and purified standards, the number of copies per ng total RNA is regarded as an approximate estimate of the number of transcripts.…”
Section: Qpcr Analysesmentioning
confidence: 99%